The Prognostic Value of Vertebral Bone Density on Chest CT in Hospitalized COVID-19 Patients - Tahtabasi, Mehmet (J Clin Densitom, 2021)
The aim of this study is to evaluate the prognostic value of the vertebral bone mineral density (BMD) on chest computed tomography (CT) in COVID-19 patients. The chest CT of hospitalized patients with COVID-19 pneumonia were evaluated for Pneumonia Severity Score (PSS) as the ratio of the volume of involved lung parenchyma to the total lung volume. In addition, BMD was manually measured from the vertebral corpus using axial CT images. The relationships of clinical variables, PSS and vertebral BMD with patient outcomes, namely mortality, intensive care unit (ICU) admission and mechanical ventilation were investigated. Lower BMD was defined as ≤100 HU. The study included 209 patients (118 males, 56.4%). As a result of the univariate analysis, the rates of mortality, ICU admission and mechanical ventilation were 17.2% (n = 36), 24.8% (n = 52), and 20.6% (n = 43), respectively, and they were significantly higher among the patients with lower BMD (38.1 vs 13.0%, p < 0.001; 33.4 vs 21.2%, p = 0.002; and 38.1 vs 8.2%, p < 0.001, respectively). In the mortality group, PSS was significantly higher (median, 9 vs 5; p < 0.001) and vertebral BMD was significantly lower (median, 83 vs 139; p < 0.001). Severe clinical incidence was significantly higher in patients with lower BMD compared to those with higher BMD (39.7 vs 24.7% and p = 0.028). There was a significant correlation between clinical classification and lower BMD (r = 0.152 and p = 0.028). The multivariate analysis revealed vertebral BMD [odds ratio (OR), 1.028; 95% CI, 1.011−1.045, p = 0.001) and lower BMD (OR, 4.682; 95% CI, 1.784−12.287, p = 0.002) as significant independent predictors of mortality. Vertebral BMD is a strong independent predictor of mortality that is reproducible and can be easily evaluated on the chest CT images of COVID-19 patients.